1999
DOI: 10.1677/jme.0.0220173
|View full text |Cite
|
Sign up to set email alerts
|

Leptin signalling in pancreatic islets and clonal insulin-secreting cells

Abstract: Leptin is a cytokine secreted from adipose tissue at a rate commensurate with the size of the body's fat stores. In addition to its anorectic and thermogenic central actions, leptin is known to act on peripheral tissues, including the pancreatic -cell where it inhibits insulin secretion and reduces insulin transcript levels. However, the role of leptin signalling through its full-length receptor, OB-Rb, in the -cell remains unclear. In the present study, we show that leptin activates a signal transducer and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
2
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 56 publications
3
29
2
3
Order By: Relevance
“…db/db Mice display obesity and type 2 diabetes, due to the absence of functional leptin receptors, the main activator of STAT3 in pancreatic b-cells (Shafrir 1992, Morton et al 1999. We have demonstrated that adult pancreatic islets, cultured with PRL, show an upregulation in STAT3 gene expression .…”
Section: Cmentioning
confidence: 81%
“…db/db Mice display obesity and type 2 diabetes, due to the absence of functional leptin receptors, the main activator of STAT3 in pancreatic b-cells (Shafrir 1992, Morton et al 1999. We have demonstrated that adult pancreatic islets, cultured with PRL, show an upregulation in STAT3 gene expression .…”
Section: Cmentioning
confidence: 81%
“…Leptin and its receptors signaling is transducted through multiple pathways, including PI3K (37), JAK-STAT3 and ERK pathways (9). To determine the downstream signaling of leptin affecting Isl-1 expression and insulin secretion, NIT cells were treated with 10 ng/ml leptin for 0, 5, 10, 20, and 30 min, and the phosphorylated STAT3 and phosphorylated ERK were analyzed by Western blot.…”
Section: Isl-1 Mediates Leptin Signaling On Insulinmentioning
confidence: 99%
“…Leptin also lowers the intracellular free calcium concentration ([Ca 2ϩ ] i ) of pancreatic beta cells (4). In addition, leptin has been shown to act through its full-length receptor (OBRb) 4 and activate the Janus kinase (JAK) and signal transducer and activator of transcription (STAT) pathway in pancreatic islets (9). The activation of OBRb induces JAK-STAT3, which is implicated in transcriptional modulation (10).…”
mentioning
confidence: 99%
“…Although STAT5 b has been shown to activate the rat I promoter through the same STAT5 motif in response to growth hormone, it is likely that leptin mediates the repression through multiple additional complexes detected in this region. Leptin activated the STAT3 pathway by increasing the phosphorylation of STAT3 and MAP Kinase pathway in RINm5F cells [174]. Thus, the importance of JAK/STAT and possibly MAP Kinase signalling pathways in the regulation of insulin gene expression by leptin is not clear.…”
Section: Nutrient and Hormonal Effects On Insulin Gene Expressionmentioning
confidence: 99%